Prevalence and Intensity of Ectoparasites on Mud Crab (Scylla serrata) in Teluk Pakedai District, Kubu Raya Regency - Helfiani Helfiani; Firman Saputra; Diah Wulandari Rousdy (Jurnal Biologi Tropis, 2023)
Mud crabs (Scylla serrata Forskal, 1775) is a species of fishery commodity that can be attacked by pathogenic agents such as ectoparasites. Ectoparasites that infect mud crabs can trigger damage to the carapace and gills at a certain number of infections. This study aims to determine the prevalence and intensity of ectoparasites in mud crabs in Selat Remis Village, Teluk Pakedai District, Kubu Raya Regency. The study was conducted by taking random samples and determining the sample size based on the Lemeshow formula (95% confidence level), then to obtain prevalence and intensity it was carried out by examining the body organs (carapace, cheliped or (pereiopod I), pereiopods (walking legs), pereiopod V (swimming legs) and gills) of mud crabs (S. serrata) and identify the species of ectoparasites. Based on the results, the average prevalence of ectoparasites in mud crabs is 45,00% included in the commonly prevalence category. The prevalence value of each ectoparasites was Vorticella (17,50%), Zoothamnium (12,50%), Octolasmis cor (12,50%), Epistylis (15%), Octolasmis angulata (7,50%) and Acineta (2,50%). The highest intensity value of ectoparasites in mud crabs was O. angulata, 28 individuals per an infected mud crab.